Assessment of Disambiguation in Translation: Indicators for an Efficient Professional Performance - Abreus González, Adrian; Escalona Falcón, Clara Alina; Tardo Fernández, Yaritza (Espergesia, 2025)
Lexical-semantic ambiguity caused by false cognates represented a common obstacle in translator training, affecting the accuracy and clarity of the translated text. This study aimed to establish evaluation indicators to assess translational performance in resolving this phenomenon. A qualitative approach was adopted, applying the holistic-dialectical method, complemented by analysis-synthesis. A linguo-didactic model was developed, integrating linguistic, cognitive, and didactic-evaluative dimensions. Based on this model, the stages of the translational process, performance descriptors, and evaluative indicators were defined, grounded in the levels of the Common European Framework of Reference for Languages, adapted to the translation context. The findings identified two levels of translational competence (basic and independent), linked to the student’s ability to identify, analyze, and disambiguate false cognates. The proposed indicators reflected clear, measurable, and applicable criteria, enhancing formative assessment. It was concluded that the incorporation of these indicators strengthened the teaching-learning process in translation by improving the quality of the translated text, fostering critical self-reflection, and ensuring a more rigorous training aligned with the professional demands of the translation field.